Normothermia for Pediatric and Congenital Heart Surgery: An Expanded Horizon - Shamsuddin, Ahmad Mahir; Nikman, Ahmad Mohd; Ali, Saedah; Zain, Mohd Rizal Mohd; Wong, Abdul Rahim; Corno, Antonio Francesco (Frontiers in Pediatrics, 2015)
Cardiopulmonary bypass (CPB) in pediatric cardiac surgery is generally performed with hypothermia, flow reduction and hemodilution. From 10/2013 to 12/2014 55 patients, median age 6 years (range 2 months to 52 years), median weight 18.5kg (range 3.2 to 57 kg), underwent surgery with normothermic high flow CPB in a new unit. There were no early or late deaths. Fifty patients (90.9%) were extubated within 3 hrs, 3 (5.5%) within 24 hrs and 2 (3.6%) within 48 hrs. Twentyfour patients (43.6%) didn’t require inotropic support, 31 (56.4%) received dopamine or dobutamine: 21 ≤5 mcg/kg/min, 8 5-10 mcg/kg/min, and 2 >10 mcg/kg/min. Two patients (6.5%) required noradrenaline 0.05-0.1 mcg/kg/min. On arrival to ICU and after 3 and 6 hrs and 8:00 am the next morning, mean lactate levels were 1.9±09, 2.0±1.2, 1.6±0.8 and 1.4±0.7 mmol/L (0.6-5.2 mmol/L) respectively. From arrival to ICU to 8:00 am the next morning mean urine output was 3.8±1.5 mL/kg/hr (0.7-7.6 mL/kg/hr), and mean chest drainage was 0.6±0.5 mL/kg/hr (0.1-2.3 mL/kg/hr). Mean ICU and hospital stay were 2.7±1.4 days (2-8 days) and 7.2±2.2 days (4-15 days) respectively. In conclusion, normothermic high flow CPB allows pediatric and congenital heart surgery with favorable outcomes even in a new unit. The immediate post-operative period is characterized by low requirement for inotropic and respiratory support, low lactate production, adequate urine output, minimal drainage from the chest drains, shorter ICU and hospital stay.